2012
DOI: 10.1111/j.1600-0447.2012.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches in bipolar disorders and the impact on cognition: a critical overview

Abstract: Pharmacotherapies for BD should be chosen to minimize neurocognitive side-effects, which may already be compromised by the disease process itself. Neurocognitive evaluation should be considered in BD patients to better evaluate treatment impact on neurocognition. A comprehensive neuropsychological evaluation also addressing potential variables and key aspects such as more severe cognitive deficits, comorbidities, differential diagnosis, and evaluation of multiple cognitive domains in longitudinal follow-up stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 152 publications
3
77
0
2
Order By: Relevance
“…Findings from present study are in line with those results suggesting that cognitive side effects should be considered when treating patients with bipolar disorder (10). A recent review advises that pharmacotherapy for bipolar disorder should be chosen to minimize cognitive side effects, which is similar to the present study (9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings from present study are in line with those results suggesting that cognitive side effects should be considered when treating patients with bipolar disorder (10). A recent review advises that pharmacotherapy for bipolar disorder should be chosen to minimize cognitive side effects, which is similar to the present study (9).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the widespread use of polypharmacy in bipolar disorder (7,8,9) makes it difficult to understand the impact of individual pharmacological components on cognition. Videira Dias et al (9) focused on the impact of pharmacotherapy on cognition in a recent systematic review. Authors suggested that lithium might have negative effects on psychomotor speed and verbal memory, and valproate was associated with attention and memory.…”
Section: Introductionmentioning
confidence: 99%
“…On another matter, an interesting issue is that most maintenance trials assessed samples enriched for efficacy; however, lamotrigine trials were unique in sense that they included study sample enriched for tolerability, and not efficacy, which may have accounted for to the high NNT detected for lamotrigine (50.4 for mania prevention and 20.2 for prevention of depression) (21,31,32,42,43). It is important to remember that polarity index is not a measure of the absolute efficacy of a drug, but it rather describes the drug profile; polarity index is a ratio, which does not provide information on NNT of each treatment, but rather tells us how balanced an intervention is.…”
Section: Discussionmentioning
confidence: 99%
“…While a small study has led to suggestions that medicated patients who are euthymic do perform similarly to those not receiving treatment,846 other naturalistic trials point towards the potential negative impact of several medications, with the effects of antipsychotics being the most significant 845. Lithium can also lead to impairment in processing speed and memory, which patients may find distressing,847 although recent randomized controlled data suggest lithium is superior to quetiapine in this regard 329. Indeed, the effects of lithium on neurocognition are complex and further research is needed to fully elucidate its neurocognitive impact 848.…”
Section: Safety and Monitoringmentioning
confidence: 99%
“…Indeed, the effects of lithium on neurocognition are complex and further research is needed to fully elucidate its neurocognitive impact 848. Anticonvulsants, except for lamotrigine, are also linked to subjective cognitive impairment 847. Given the importance of cognition on a patient's function and quality of life, further studies are needed in this area.…”
Section: Safety and Monitoringmentioning
confidence: 99%